2017
DOI: 10.1186/s13640-017-0211-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Sixteen Personality Factors (16PF) of an individual by analyzing facial features

Abstract: We propose a novel three-layered neural network-based architecture for predicting the Sixteen Personality Factors from facial features analyzed using Facial Action Coding System. The proposed architecture is built on three layers: a base layer where the facial features are extracted from each video frame using a multi-state face model and the intensity levels of 27 Action Units (AUs) are computed, an intermediary level where an AU activity map is built containing all AUs' intensity levels fetched from the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The following study verified that facial expressions on videos implicated 442 participants and achieved accuracy at minimum 5 and 83.5% for maximum (Teijeiro-Mosquera et al, 2014). Another investigation foresees facial expressions showing emotion implicated 64 participants using 16 PF reached validity for predictive at 80% (Gavrilescu and Vizireanu, 2017). Another research carried out 186 datasets used in facial expressions reached a prediction accuracy minimum at 53.37 and maximum at 82.02% with twenty different classes involved (Zhang et al, 2017).…”
Section: Introductionsupporting
confidence: 60%
“…The following study verified that facial expressions on videos implicated 442 participants and achieved accuracy at minimum 5 and 83.5% for maximum (Teijeiro-Mosquera et al, 2014). Another investigation foresees facial expressions showing emotion implicated 64 participants using 16 PF reached validity for predictive at 80% (Gavrilescu and Vizireanu, 2017). Another research carried out 186 datasets used in facial expressions reached a prediction accuracy minimum at 53.37 and maximum at 82.02% with twenty different classes involved (Zhang et al, 2017).…”
Section: Introductionsupporting
confidence: 60%
“…[7] investigated the physiological correlation of emotion and personality using commercial sensors and found that the emotion-to-personality relationship is better captured by non-linear rather than linear statistics. [8] proposed a threelayer neural network-based architecture for predicting the sixteen personality factors from faces analyzed using facial action coding system.…”
Section: Introductionmentioning
confidence: 99%
“…Although personality traits appear to be somewhat predictable, there can be variations in predictions for the same person and different face images, e.g., due to facial expression and pose [62,45,72,61]. For automated recognition of personality traits, two deep learning methods have been presented where accuracies between 50 % and 80 % were reported for different personality traits [76,23], measured by the 16 Personality Factors model. Also, a patent was filed recently for automatic personality and capability prediction from faces [66].…”
Section: Related Workmentioning
confidence: 99%
“…Also, predicting more subjective quantities such as facial beauty has been studied with machine learning methods [70,21]. Even more subtle attributes such as self-reported personality traits have been investigated in terms of their predictability from face images with deep learning methods [76,23]. Thus, a variety of properties have been automatically derived from face images.…”
Section: Introductionmentioning
confidence: 99%